2012
DOI: 10.1037/a0024787
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception measures' associations with behavior intentions, affect, and cognition following colon cancer screening messages.

Abstract: Researchers interested in risk perception should assess feelings-of-risk along with more traditional measures. Those interested in influencing health behavior specifically should attempt to increase feelings of vulnerability rather than numerical risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(144 citation statements)
references
References 49 publications
10
126
1
Order By: Relevance
“…Part of the explanation for the low predictive value of perceived risk may be failure to control for past and anticipated future screening behavior in cross-sectional studies (Weinstein & Nicolich, 1993) and heterogeneous measurement of risk perceptions (Vernon, 1999). A recent study comparing different measures of perceived risk found that the "feelings of risk" item "If I don't get screened, I would feel very vulnerable to getting colon cancer sometime in my life" had the strongest association with colonoscopy intention (Dillard, Ferrer, Ubel, & Fagerlin, 2012). The relationship with screening behavior is yet to be explored, although a study of vaccination found that "feelings of risk" was a stronger predictor than were other measures of risk probability (Weinstein et al, 2007), and it is clear that affective responses to risk information play a major role in decision making (Slovic, Peters, Finucane, & Macgregor, 2005).…”
Section: Individual Determinants Of Cancer Screening Participationmentioning
confidence: 99%
“…Part of the explanation for the low predictive value of perceived risk may be failure to control for past and anticipated future screening behavior in cross-sectional studies (Weinstein & Nicolich, 1993) and heterogeneous measurement of risk perceptions (Vernon, 1999). A recent study comparing different measures of perceived risk found that the "feelings of risk" item "If I don't get screened, I would feel very vulnerable to getting colon cancer sometime in my life" had the strongest association with colonoscopy intention (Dillard, Ferrer, Ubel, & Fagerlin, 2012). The relationship with screening behavior is yet to be explored, although a study of vaccination found that "feelings of risk" was a stronger predictor than were other measures of risk probability (Weinstein et al, 2007), and it is clear that affective responses to risk information play a major role in decision making (Slovic, Peters, Finucane, & Macgregor, 2005).…”
Section: Individual Determinants Of Cancer Screening Participationmentioning
confidence: 99%
“…In that analysis, absolute verbal risk perception and "feeling-of-risk" were significant predictors of intent to get a test in the next year, but the absolute numerical risk and comparative measures were not. 19 In our study, we found that the comparative measure of "higher than average" risk was a significant predictor of intent to receive screening for personal benefit, but we did not ask about "feelings-of-risk". Risk perception is different than actual risk; thus, a person who perceives herself to be at increased risk may or may not actually be at increased risk.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have shown that personal risk perception is an important factor in motivating individuals to obtain cancer screening, although the optimal measure of risk perception is not clear. 5,19 In a recent study of risk perception and colorectal cancer screening with 1,628 persons (51 % women, 75 % White), participants read messages about the importance of screening to reduce the risk of cancer. Perceived risk was evaluated with four measures: absolute numerical scale, absolute verbal scale, a comparative measure and a "feelings-of-risk" measure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, psychologists may use an experimental design to investigate the impact of the manipulation of factors (such as type of information provided) on cognitions, intentions and behaviour related to screening uptake, and thereby provide those overseeing screening programmes with evidence to guide the design of promotional material and invitations to participate in a programme (for example, Dillard et al 2011, Marteau et al 2010. In contrast, sociological critiques (such as surveillance and medicalisation) may question a screening programme's materials, and in turn its purpose, as we will describe in the next section.…”
Section: Why Does Screening Merit Sociological Attention?mentioning
confidence: 99%